O BOLSONARISMO COMO UM MOVIMENTO POLÍTICO TOTALITÁRIO (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
This article seeks to analyze the political movement of unrestricted support for President Jair Bolsonaro, the so-called Bolsonarism, as a political movement with a totalitarian bias. To this end, Hannah Arendt's definition of totalitarianism will be adopted in her book “The Origins of Totalitarianism”, complemented by the interpretations of Celso Lafer and Norberto Bobbio on the subject. Based on the elements of the totalitarian regime, proposed based on the thoughts of these authors, an analysis of the current situation in social networks and other media outlets will be carried out, as well as the behavior of President Jair Bolsonaro with regard to his supporters. The method used is deductive and the technique is the bibliography and the analysis of the situation in stages by Herbert de Souza. It was concluded that Bolsonarism is configured as a totalitarian movement with characteristics of the election of enemies of the nation, worship of the leader, permanent mobilization, and structure of the movement